Evaluating Film’s Efficacy in Improving Individuals’ Attitudes and Knowledge About Maternal Health in Sierra Leone - Erickson, Brooke; Mulligan, Constance; Le Vu, MJ; Kamara, Musa Santigie; Wakeel, Fathima; Kramp, Michael (Journal of Maternal and Child Health, 2025)
Background: Sierra Leone’s high maternal mortality rate is attributed to inadequate healthcare, low health literacy, and distrust in healthcare facilities. The Mothers of Sierra Leone team produces films to empower women, improve maternal health attitudes, and facilitate care-seeking behaviors. This study quantifies the efficacy of two educational films on Sierra Leonean mothers’ and fathers’ health-related knowledge and beliefs. Subjects and Method: This pre- and post-survey study was conducted in Makeni and Freetown, Sierra Leone, with 76 participants recruited through convenience sampling - 19 mothers and 19 fathers in both film groups. Participants viewed films on either family planning or maternal mental health. The independent variables included the film subject, family planning, or maternal mental health, and the dependent variables involved changes in knowledge, attitudes, and behavior from pre- to post-intervention. Measurement instruments included surveys with questions on a Likert scale. Statistical analyses were performed in RStudio, using Wilcoxon Signed-Rank, Mann-Whitney, Fisher’s exact, and Spearman’s Rho tests to assess post-intervention changes and the efficacy of the films. Results: Findings revealed a 20.8% increase in perceived understanding (p = 0.02), a 61.1% increase in willingness to seek family planning services (p = 0.03) in mothers, and a 20.9% increase in the likelihood of managing mental health (p = 0.01) in mothers. Fathers’ willingness to be involved in their partners’ healthcare increased by 53.4% (p < 0.001). The family planning film was better received than the mental health film (U = 121.5, p = 0.03). Gender differences were observed, with fathers more inclined (p < 0.001) to address their mental health compared to mothers. Conclusion: Leveraging film as an educational tool to amplify community members’ stories can enhance health literacy, improve attitudes and behaviors, and support maternal health outcomes.